Produção de juvenis de Artemia franciscana e análise da utilização de dietas vivas e inertes na larvicultura intensiva do pintado Pseudoplatystoma coruscans - Takata, Rodrigo [UNESP] (2007)
The intensive cultivation of Artemia franciscana is an activity carried out in some countries with relative success; however this activity is not so expressive in Brazil. The aim of this work was to standardize the cultivation technology of Artemia juveniles in regions that are distant from the seashore, using only NaCl for salinization of the water and different diets, salinity rates and temperatures. One carried out three experiments by which the brans of soybeans, rice and wheat, fresh and dried yeast, grinded oat; salinity of 10‰, 20‰, 25‰, 30‰, 35‰ and temperatures of 20oC, 25oC and 30oC. The experimental period lasted for ten days in every experiment, and the feeding was done twice a day, offering 0,2g/L from the first until the sixth and 0,35g/L from the seventh to the tenth day. The survival rate and biomass production were also evaluated. The soybean bran did not show satisfactory results, being that not a single live Artemia was found in this treatment after the experimental period. However, on the other treatments, one observed the same tendencies for the survival as well as for biomass production, with a distinction to the oat bran treatment that came to be statistically superior compared to the other diets. In the salinity experiment, no live Artemia were observed after ten days of cultivation at a concentration of 10‰. Both 30‰ and 35‰ salinity rates outstood (P<0,05) over the 20‰ and 25‰ concentrations, which did not present any differences among each other (P>0,05). Regarding the temperature, the best averages for survival were obtained with an intermediate temperature (25oC); however not different (P>0,05) from the highest temperature (30oC). The 20oC temperature presented statistically inferior (P>0,05) survival and biomass production rates in comparison to the other temperatures...